Objective assessment of blood and lymphatic vessel invasion and association with macrophage infiltration in cutaneous melanoma - Storr, Sarah J.; Safuan, Sabreena; Mitra, Angana; Elliott, Faye; Walker, Christopher; Vasko, Mark J.; Ho, Bernard; Cook, Martin; Mohammed, Rabab A.A.; Patel, Poulam M.; Ellis, Ian O.; Newton-Bishop, Julia A.; et al. (Nature Publishing Group, 2011)
The aims of this study were to investigate the role of vascular invasion (blood and lymphatic), vessel density and the presence of tumour-associated macrophages as prognostic markers in 202 cutaneous melanoma patients. Sections of primary melanoma were stained with lymphatic-specific antibody D2-40 to assess lymphatic vessel invasion and density in intratumoural and peritumoural areas; an antibody against endothelial marker CD34 was used to determine blood vessel invasion and density, and an antibody against CD68 was used to determine macrophage counts. Immunohistochemically determined vascular invasion (combined blood and lymphatic) was compared with that determined using haematoxylin and eosin (H&E) staining. The use of immunohistochemistry increased detection of vascular invasion from 8–30% of patients, and histological exam of H&E-stained tissue was associated with a false positive rate of 64%. Lymphatic vessel invasion occurred at a much higher frequency than blood vessel invasion (27 and 4% of patients, respectively). Although immunohistochemically detected vessel invasion was significantly associated with histological markers of adverse prognosis, such as increased Breslow thickness, ulceration and mitotic rate (all P<0.001), no associations with relapse-free or overall survival were observed. High macrophage counts were significantly associated with markers of aggressive disease, such as Breslow thickness, ulceration and mitotic rate (P<0.001, P<0.001, P=0.005, respectively), and lymphatic vessel invasion and high microvessel density (P=0.002 and P=0.003, respectively). These results suggest that vascular invasion is more accurately detected using immunohistochemistry and occurs predominantly via lymphatic vessels. The association of vessel characteristics with histological characteristics of the primary melanoma provides evidence for their biological importance in melanoma, but that they were not associated with clinical outcome attests to the value of existing histological prognostic biomarkers. We note that a high macrophage count may be associated with neovascularisation and primary tumour growth, and may also promote invasion through lymphatic vessels.